Planning for Empire : Reform Bureaucrats and the Japanese Wartime State - Mimura, Janis, 1963- (Book collections on Project MUSE., 2011)
Japan's invasion of Manchuria in September of 1931 initiated a new phase of brutal occupation and warfare in Asia and the Pacific. It forwarded the project of remaking the Japanese state along technocratic and fascistic lines and creating a self-sufficient Asian bloc centered on Japan and its puppet state of Manchukuo. In Planning for Empire, Janis Mimura traces the origins and evolution of this new order and the ideas and policies of its chief architects, the reform bureaucrats. The reform bureaucrats pursued a radical, authoritarian vision of modern Japan in which public and private spheres were fused, ownership and control of capital were separated, and society was ruled by technocrats. Mimura shifts our attention away from reactionary young officers to state planners-reform bureaucrats, total war officers, new zaibatsu leaders, economists, political scientists, engineers, and labor party leaders. She shows how empire building and war mobilization raised the stature and influence of these middle-class professionals by calling forth new government planning agencies, research bureaus, and think tanks to draft Five Year industrial plans, rationalize industry, mobilize the masses, streamline the bureaucracy, and manage big business. Deftly examining the political battles and compromises of Japanese technocrats in their bid for political power and Asian hegemony, Planning for Empire offers a new perspective on Japanese fascism by revealing its modern roots in the close interaction of technology and right-wing ideology.